Підсумки, проблеми і перспективи вивчення кераміки Середньої Наддніпрянщини ІІ-ї половини ХІІІ — XVIII ст. - Оногда, О.В.; Чекановський, А.А.; Чміль, Л.В. (Археологія і давня історія України, 2010)
У роботі подано короткі результати дослідження кераміки Середньої Наддніпрянщини др.
пол. ХІІІ — ХVІІІ ст. на сучасному етапі. Зроблено огляд наукових праць з даної теми. Окреслено актуальні напрямки у вивченні пізньосередньовічної кераміки цього регіону. В публикации рассмотрены основные результаты
исследований керамики Среднего Поднепровья второй половины ХIII—XVIII вв., сделан обзор основных
достижений исследователей смежных дисциплин:
этнографов и искусствоведов. Объектом целенаправленного изучения археологов керамика данного периода стала относительно недавно. Это связанно со спецификой накопления источниковедческой базы.
В настоящий момент можно обозначить три основных
направления исследований: 1) публикации материалов отдельных памятников, содержащие описание
керамики; 2) работы, посвященные систематизации
керамики с отдельных территорий или музейных коллекций; 3) исследования, посвященные проблемным
вопросам керамического производства. Краткий анализ истории изучения керамики данного периода позволил выделить наименее исследованные и наиболее перспективные аспекты дальнейшего ее изучения. The article surveys main results of investigations of
the Middle Dnipro region pottery dating from the second
half of XIII to XVIII cent. It reviews main achievements of
sub-discipline researches, including ethnographic and art
history explorations. Mentioned period’s pottery started
to be an object of purposeful archaeological investigation
quite recently. This happened due to the specific character
of the archaeological sources data. Three main branches
of investigation can be outlined for the present moment:
1) publications of separate sites results of excavations,
which include pottery description; 2) the researches concentrated
on systematization pottery from separate locations
or museum collections; 3) investigations dedicated
to the problematic questions of pottery production. Brief
analysis of the history of pottery investigation allows to
outline the least explored and thus the most perspective
aspects of its further investigation.